1996
DOI: 10.1093/ije/25.4.862
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemic of Visceral Leishmaniasis in Western Upper Nile, Southern Sudan: Course and Impact from 1984 to 1994

Abstract: This continuing epidemic has shown that VL can cause high mortality in an outbreak with astonishingly high infection rates. Population movement has been a major factor in transmission and poor nutritional status has probably contributed to the risk of clinical infection. Although over 17,000 people have been successfully treated for VL at the clinics in WUN, the disease is likely to become endemic there.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
111
0
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(115 citation statements)
references
References 14 publications
0
111
0
4
Order By: Relevance
“…In the northern focus (Upper Nile, Jonglei, and Unity states), Phlebotomus orientalis is the vector; in the southern focus (parts of Eastern Equatoria state), P. martini is the vector (3,4). Although studies in eastern Sudan have found domestic animals infected with the parasite (5,6), whether these animals play a role as disease reservoirs has not yet been proven; thus, transmission is still thought to be anthroponotic.…”
Section: The Reviewmentioning
confidence: 99%
“…In the northern focus (Upper Nile, Jonglei, and Unity states), Phlebotomus orientalis is the vector; in the southern focus (parts of Eastern Equatoria state), P. martini is the vector (3,4). Although studies in eastern Sudan have found domestic animals infected with the parasite (5,6), whether these animals play a role as disease reservoirs has not yet been proven; thus, transmission is still thought to be anthroponotic.…”
Section: The Reviewmentioning
confidence: 99%
“…One of the more recent ones of almost unimaginable proportions was the epidemic of VL in the Southern Sudan, known as the Western Upper Nile (WUN) region (Seaman et al 1996). People found themselves in the middle of a civil war which impeded diagnosis and treatment.…”
Section: Civilians In War and Social Unrestmentioning
confidence: 99%
“…chagasi, the causative agents of visceral leishmaniasis (VL), 3 may result in subclinical infection, or progress to a fatal outcome (1,2). Epidemics of VL continue to exact a significant human toll in developing countries, notably in the Sudan, where overall death rates of 38 -57% have been recorded in recent years (2).…”
Section: H Uman Infection With Leishmania Donovani and Leishmaniamentioning
confidence: 99%
“…Epidemics of VL continue to exact a significant human toll in developing countries, notably in the Sudan, where overall death rates of 38 -57% have been recorded in recent years (2). Although the immunology of VL has received considerable attention (3)(4)(5)(6)(7), efforts toward vaccination against leishmaniasis have focused almost exclusively on localized cutaneous disease (8 -11).…”
Section: H Uman Infection With Leishmania Donovani and Leishmaniamentioning
confidence: 99%